The MERS-CoV N Protein Regulates Host Cytokinesis and Protein Translation via Interaction With EF1A - Zhu, Lin; Gao, Ting; Fu, Yangbo; Han, Xiujing; Yue, Junjie; Liu, Yaoning; Liu, Hainan; Dong, Qincai; Yang, Weihong; Hu, Yong; Jin, Yanwen; Li, Ping; et al. (Frontiers in Microbiology, 2021)
Middle East respiratory syndrome coronavirus (MERS-CoV), a pathogen causing severe respiratory disease in humans that emerged in June 2012, is a novel beta coronavirus similar to severe acute respiratory syndrome coronavirus (SARS-CoV). In this study, immunoprecipitation and proximity ligation assays revealed that the nucleocapsid (N) protein of MERS-CoV interacted with human translation elongation factor 1A (EF1A), an essential component of the translation system with important roles in protein translation, cytokinesis, and filamentous actin (F-actin) bundling. The C-terminal motif (residues 359-363) of the N protein was the crucial domain involved in this interaction. The interaction between the MERS-CoV N protein and EF1A resulted in cytokinesis inhibition due to the formation of inactive F-actin bundles, as observed in an in vitro actin polymerization assay and in MERS-CoV-infected cells. Furthermore, the translation of a CoV-like reporter mRNA carrying the MERS-CoV 5’UTR was significantly potentiated by the N protein, indicating that a similar process may contribute to EF1A-associated viral protein translation. This study highlights the crucial role of EF1A in MERS-CoV infection and provides new insights into the pathogenesis of coronavirus infections.